2017
DOI: 10.21873/anticanres.11590
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Therapy Sequence with Alkylating Agents and MGMT Status in Patients with Advanced Neuroendocrine Tumors

Abstract: Upfront chemotherapy with either STZ-based treatment or DTIC monotherapy showed similar efficacy and median TTP rates. In this study, MGMT protein expression assessed by immunohistochemistry did not play an important role as a predictive marker for alkylating agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 37 publications
(46 reference statements)
1
16
0
Order By: Relevance
“…Nevertheless, previous studies concerning the role of MGMT status in NENs reported contrasting results. In two previous studies [15,19,[29][30][31] no correlation was found between MGMT status and response to TEM. In three other studies [16,18,20], a predictive value was found only in the sub-group of pancreatic NENs.…”
Section: Discussionmentioning
confidence: 91%
“…Nevertheless, previous studies concerning the role of MGMT status in NENs reported contrasting results. In two previous studies [15,19,[29][30][31] no correlation was found between MGMT status and response to TEM. In three other studies [16,18,20], a predictive value was found only in the sub-group of pancreatic NENs.…”
Section: Discussionmentioning
confidence: 91%
“…It is important to note that these studies were heterogeneous and often small, with NET of various origins. Nevertheless, the efficacy of DTIC-based chemotherapy was higher in patients with pNET (36–50%) compared to NET from other sites [22, 24, 27, 28, 30]. …”
Section: Discussionmentioning
confidence: 98%
“…This study reported an ORR of 27%, but no results on survival. In addition, other studies exploring DTIC alone reported an ORR of 8–50% (pooled mean, 20%) with limited or no survival data [17-24]. More recently, 5 studies reported an increased efficacy of the 5FU-DTIC-epirubicin combination with an ORR ranging from 17 to 56% (pooled mean, 31%), and a median PFS varying from 5 to 21 months [25-29].…”
Section: Discussionmentioning
confidence: 99%
“…The following articles were excluded for the following reasons: NENs patients were not included (n = 11); undesired outcomes (n = 6); non-MGMT gene study (n = 4); reviews (n = 2); and study protocol (n = 1). Therefore, 11 studies were included in this meta-analysis [16,17,[19][20][21][22][23][24][25][26][27] (Figure 1 and Table 1). Abbreviations: GI, gastrointestinal; IHC, immunohistochemistry; MSP, methylation-specific polymerase chain reaction; NE, neuroendocrine tumours; NEN, neuroendocrine neoplasm; NOS, Newcastle-Ottawa Scale; PDEC, poorly differentiated endocrine carcinoma; PSQ, pyrosequencing.…”
Section: Resultsmentioning
confidence: 99%